Bank mergers and acquisitions and the post-merger and acquisition performance of combined banks: evidence from Sub-Saharan Africa - Ayagre, P.; Aboagye, A.Q.Q.; Sarpong-Kumankoma, E.; Asuming, P.O. (Cogent Economics & Finance, 2024)
This study sought to ascertain the effects of bank mergers and acquisitions on the performance of merged banks in Sub-Saharan African (SSA) countries between 2003 and 2019. Specifically, the study aimed to investigate the impact of regulation-induced bank mergers and acquisitions (M&A’s) on the post-merger profitability of merged banks in SSA. The motivation for the study is to provide evidence for or against the regulator’s claims that regulation-induced bank M&As will improve the performance of merged banks in SSA. The article presents the results of the total sample of all mergers and acquisitions examined in the study and two sub-samples: the regulation-induced M&A sub-sample and the voluntary M&A sub-sample. We measure profitability by return on assets, return on equity, and net interest margin. The paper employed a dynamic panel Generalized Methods of Moments approach to analyse the relationship between bank M&As and profitability. The study found no profitability improvement after M&A across all profitability measures for the total sample and the two sub-samples. Instead, the empirical results reveal that bank profitability suffers after mergers and acquisitions across all profitability measures. The results show that, for regulation-induced mergers and acquisitions, a merged bank’s profitability is adversely affected from the beginning of the merger or acquisition to the sixth year of mergers and acquisitions. The findings also reveal that bank risk negatively affect profitability, while liquidity positively affect profitability, except returns on equity. Bank costs-to-income ratios as expected to show negative relationship with profitability. All macroeconomic variables show the expected relationship, positive for GDP growth and negative for inflation
Research Article
Keywords: Sub-Saharan Africa; Bank; performance